Regulation of epigenetic traits of the glutathione S-transferase P1 gene: from detoxification toward cancer prevention and diagnosis - Schnekenburger, Michael; Karius, Tommy; Diederich, Marc (Frontiers in Pharmacology, 2014)
Glutathione S-transferases (GSTs) are phase II drug detoxifying enzymes that play an essential role in maintenance of cell integrity and protection against DNA damage by catalyzing the conjugation of glutathione to a wide variety of exo- and endogenous electrophilic substrates. GSTP1, the gene encoding the piclass GST is frequently inactivated by acquired somatic CpG island promoter hypermethylation in multiple cancer subtypes including prostate, breast, liver and blood cancers. Epigenetically mediated GSTP1 silencing is associated with enhanced cancer susceptibility by decreasing its “caretaker” gene function, which tends to promote neoplastic transformation allowing the cell to acquire additional alterations. Thus, this epigenetic alteration is now considered as a cancer biomarker but could as well play a driving role in multistep cancer development especially well documented in prostate cancer development. The present review discusses application of epigenetic alterations affecting GSTP1 in cancer medicine used alone or in combination with other biomarkers for cancer detection and diagnosis as well as for future targeted preventive and therapeutic interventions including by dietary agents.